Hierarchical Ni(OH)2–MnO2 hollow spheres as an electrode material for high-performance supercapacitors. Issue 14 (13th June 2022) - Wei, Chengzhen; Sun, Jun; Zhang, Yuchen; Liu, Yue; Guo, Zhencai; Du, Weimin; Liu, Lin; Zhang, Yongming
Abstract : Hierarchical Ni(OH)2 –MnO2 hollow spheres are prepared via a simple self-templating route. The structural and compositional advantages of the Ni(OH)2 –MnO2 material endow it with remarkable performance as a supercapacitor. Abstract : Hybrid electrode materials with hollow structures are incredibly attractive for energy storage owing to the synergies between the different materials used in their fabrication and the structural advantages they offer. Here we demonstrate a self-templating strategy to prepare hierarchical Ni(OH)2 –MnO2 hollow spheres. First, Ni–Mn glycerate solid spheres are fabricated as the template and then chemically transformed into hierarchical Ni–Mn hydroxide hollow structures. Finally, hierarchical Ni(OH)2 –MnO2 hollow spheres are obtained via oxidation of the Ni–Mn hydroxide with O2 . These unique structures endow the Ni(OH)2 –MnO2 material with many inner cavities, a high surface area and more electroactive sites. As an electrode material for supercapacitors, a large capacitance of 2086.6 F g −1 is obtained at 2.0 A g −1, and this can reach as high as 972.8 F g −1, even at 20 A g −1 . Moreover, the hierarchical Ni(OH)2 –MnO2 hollow spheres also have a remarkable rate capability and good cycling durability (only 11.5% capacitance reduction over 5000 cycles at 15 A g −1 ). A solid-state asymmetric supercapacitor device is constructed from the hierarchical Ni(OH)2 –MnO2 hollow spheres and activated carbon. The device shows a high energy density of 68.7 W h kg −1 versus a power density of 1650 W kg −1 at 2.0 A g −1 . The energy density remains at 25.8 W h kg −1 versus a power density of 12 372 W kg −1 at 15 A g −1 . We envision that this work will not only offer a promising electrode material for supercapacitors but will also provide an alternative avenue to prepare hollow structured materials.